Adaptation of The Abusive Supervision Scale with Indonesian Version - Muhammad Indra Astrawan; Rifan Alamsyah (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
Abusive supervision can have a negative impact on employee welfare and performance. Unfortunately, there are still very few questionnaires available that can measure abusive supervision in a standardized and psychometrically tested Indonesian language version. Therefore, the purpose of this study is to adapt and test the validity and reliability of the abusive supervision measurement tool in Indonesian. The population in this study consisted of 1,280 cigarette production workers, with the sample calculated using the Slovin formula at a 5% error rate, resulting in a minimum of 304 respondents. In this study, the researchers successfully involved 486 participants as research subjects using purposive sampling. The analysis used in this study was confirmatory factor analysis to test whether the data obtained by the researchers was in accordance with the predetermined measurement model in order to test the construct validity of the measurement tool. The results of this study indicate that the fit index parameters have been met (GFI = 0.984, RMSEA = 0.054, SRMR = 0.029, NFI = 0.961, CFI = 0.976, & TLI = 0.967). The reliability test results using the ω coefficient (0.892) and α coefficient (0.884) show excellent results. However, one dimension of abusive supervision, namely credit stealing, has a reliability value (ω = 0.110 & α = 0.111) and validity (AVE = 0.292) that are less than ideal. The implication of this study is the availability of an Indonesian version of the abusive supervision measurement tool that can be used to assess the harsh behavior of supervisors in the Indonesian work context. The suggestion for future researchers is that it is very necessary to further develop and test the items in the credit stealing dimension.